Generic types of competitive strategies in the polish retail industry - Pilarczyk, B.; Stefanska, М. (Видавництво Львівської політехніки, 2013)
The aim of the paper is to indicate the evolution of competitive strategies implemented by retail chains (particularly foreign ones) on the Polish market. The basic incentive to choose them is aiming at achieving competitive advantage on international and global scale. Generic strategies defined by M. Porter – strategies of cost leadership, product differentiation and focus constitute the theoretical background for the discussion. Work is funded by the NCN grant based on the decision number DEC-2011/03/B/HS4/03576. Вказано на еволюцію конкурентоспроможних стратегій, які застосовуються у межах роздрібних ланцюгів (особливо, іноземних) на Польському ринку. Основною причиною вибору теми є висвітлення можливостей досягнення конкурентних переваг у міжнародному і у глобальному масштабі. Загальні стратегії, визначені M. Портером, стратегії лідерства за витратами, диференціації продукції становлять теоретичну основу для обговорення. Робота профінансована за кошти гранту на основі NCN рішення DEC-2011/03/B/HS4/03576.
Загальні види конкурентних стратегій у польській роздрібній торгівлі
Keywords: evolution of retail industry; competitive strategies; еволюція роздрібної торгівлі; конкурентоспроможні стратегії